Journal Info - Board, Editorial (Law, State and Telecommunications Review, 2022)
DOI: https://doi.org/10.26512/lstr.v14i1 SCOPUS Q3 - MIAR Index 9.6 - SJR H-Index 4 Editor: Prof. Marcio Iorio Aranha (University of Brasilia, BRAZIL) Editorial Board: Prof. Marcio Iorio Aranha (University of Brasilia – BRAZIL), Prof. André Rossi (Utah Valley University - USA), Prof. Ana Frazao (Universidade de Brasilia - BRAZIL), Prof. Clara Luz Alvarez (Universidad Panamericana - MEXICO), Prof. Diego Cardona (Universidad de Rosario - COLOMBIA), Prof. Flavia M. S. Oliveira (Universidade de Brasilia - BRAZIL) Prof. Francisco Sierra Caballero (Universidad de Sevilla - SPAIN), Prof. Fabio Bassan (Universitá degli Studi Roma Tre - ITALIA), Prof. Hernán Galperin (University of Southern California - USA), Prof. Jerônimo Siqueira Tybusch (Universidade Federal de Santa Maria - BRAZIL), Prof. João Alberto de Oliveira Lima (Universidade do Legislativo Brasileiro - BRAZIL), Prof. Judith Mariscal (CIDE - MEXICO), Prof. Liliana Ruiz de Alonso (Universidad San Martín de Porres - PERU), Prof. Lucas Sierra (Universidad de Chile - CHILE), Prof. Luís Fernando Ramos Molinaro (Universidade de Brasília - BRAZIL), Prof. Murilo César Ramos (Universidade de Brasília - BRAZIL), Prof. Raúl Katz (Columbia University - USA), Prof. Roberto Muñoz (Universidad Técnica - CHILE). ISSN: 1984-9729 EISSN: 1984-8161 Periodicity: annual issues uninterrupted since May 2009 and two annual issues on May and October uninterrupted since May 2018. Mission/Scope/Focus: http://periodicos.unb.br/index.php/RDET/about Submission process: authors are requested to submit their papers following the instructions at http://periodicos.unb.br/index.php/RDET/about/submissions. The journal adopts the double-blind peer review process. Archiving policy: LOCKSS-CARINIANA, DOAJ and Brazil’s Senate Library. Indexation: SCOPUS (Elsevier); CROSSREF; ROAD; THE KEEPERS; LATINDEX (28283); EBSCOhost research databases (EBSCO Publishing Inc.); Gale Group; AE Global Index; OAI (Open Archives Initiative) - DOAJ (Directory of Open Access Journals); WorldCat; Google Scholar; The European Library; CIEPS (Centre International d’Enregistrement des Publications en Série); Sistemas SEER e Diadorim, do IBICT. Permanent Web Identifier: LexML and DOI. Manuscript Submission Process Authors, please submit here: http://periodicos.unb.br/index.php/RDET/about/submissions Submission time frame: The L.S.T.R. submission process is open all year round. Papers selected will be tentatively scheduled for publishing in the next issue. Languages accepted: English, Spanish and Portuguese. Formal requirements: The easiest way to follow this journal’s formal requirements is to download the template in English from the L.S.T.R. website, in the section “Author Guidelines” and replace the content with your own material. The template file contains specially formatted styles (e.g., Normal, Heading, Footer, Abstract, Subtle Emphasis, and Intense Emphasis) that will reduce the work in formatting your final submission. The following instructions are already embedded in the template, but they are transcribed below in case you prefer to apply them directly to your paper. Please use the following coordinates for the page setup: Top (1.93 cm); Bottom (1.93 cm); Inside (1,93 cm); Outside (1,52 cm); Gutter (0,36 cm); mirror margins; page size customized for width (15,24 cm) and height (22,86 cm); different odd and even pages; Layout from Edge (Header: 0,89 cm; Footer: 0,76 cm). Right margins should be justified, not ragged. Please use a 10-point Times New Roman font or, if it is unavailable, another proportional font with serifs, as close as possible in appearance to Times New Roman 10-point. On a Macintosh, use the font named Times and not Times New Roman. Also, quotations of more than two lines should be written in Times New Roman, 10, scale 90%, line spacing exactly 10 pt. Legal texts should be cited as Times New Roman, 10, scale 80%, line spacing exactly 10 pt, “Don’t add space between paragraphs of the same style” marked, indentation left 1.78 cm and right 1.78 cm. For reference purpose, please use the ABNT NBR style or APA. Structured abstract: The L.S.T.R. adopts structured abstracts embedded in the template below. Template: https://periodicos.unb.br/index.php/RDET/information/authors.